Pengaruh Transaksi Pihak Berelasi, Beban Iklan, dan Kompensasi Eksekutif terhadap Agresivitas Pajak - Rika Nazil Ainiyah; Judi Budiman (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Tax aggressiveness is prevalent among consumer cyclicals sector companies that contribute significantly to the national economy. This research examines the effect of related-party transactions, advertising expenses, and executive compensation on tax aggressiveness in consumer cyclicals sector companies listed on the Indonesia Stock Exchange during 2022-2024. This study employed a quantitative research method using secondary data from financial statements. The population consisted of 168 consumer cyclicals companies, with 56 observations selected through purposive sampling. Data analysis used multiple linear regression analysis via SPSS 26, including descriptive statistics testing, classical assumption testing, goodness of fit model testing, and hypothesis testing. Results reveal that simultaneously, all three independent variables significantly influence tax aggressiveness (F=6.722; sig.=0.001). Partially, related-party transactions do not significantly affect tax aggressiveness (t=-0.257; sig.=0.798), advertising expenses negatively influence tax aggressiveness (t=-2.444; sig.=0.018), and executive compensation positively affects tax aggressiveness (t=3.601; sig.=0.001). The adjusted R² value of 0.241 indicates that independent variables explain 24.1% of tax aggressiveness variation. In conclusion, advertising expenses and executive compensation serve as significant determinants of tax aggressiveness, while related-party transactions show no significant effect. However, only 24.1% of tax aggressiveness variation is explained by these variables, suggesting other factors require investigation in future research.